Navigation and Guidance of Orbital Transfer Vehicle - Li, Xuefeng (Navigation: Science and Technology,, 2018)
This book uses the entire flying process, starting from ground launching of the orbital transfer vehicle (OTV) to injecting payload into earth synchronous orbit, as an example for real-world engineering practices. It discusses in detail the analysis design and integrated OTV navigation and guidance system technologies in combination with the engineering experiences of the authors in analysis, design and integrated OTV navigation and guidance system applications, and the research on navigation and guidance theories. It focuses on establishing motion of air vehicle equations, control system hardware components, orbit prediction technology, inertial navigation and initial alignment technologies, INS/GNSS integrated navigation technologies, INS/CNS integrated navigation technologies, redundant fault tolerance and failure reconfiguration technology of inertial sensors, guidance and midcourse correction technologies and orbit control strategies. The book is a valuable reference book for the engineers, technicians and researchers who are engaged in analysis, design and integrated application of OTV navigation and guidance control systems. It can also be used as teaching material for postgraduates and senior undergraduates majoring in OTV navigation and guidance systems and other related subjects.